Collaborative Use Repurposing Engine (CURE): FDA-NCATS/NIH Effort to Capture the Global Clinical Experience of Drug Repurposing to Facilitate Development of New Treatments for Neglected and Emerging Infectious Diseases. (4th October 2017) - Stone, Heather; Sacks, Leonard; Tiernan, Rosemary; Duggal, Mili; Sheils, Timothy; Southall, Noel
Abstract: Background: Repurposing approved products has proven a critical strategy to serve unmet medical needs. Historically, 40% of drugs approved for treatment of tropical diseases were repurposed, including albendazole for echinococcosis and neurocysticercosis, and azithromycin for trachoma. Advantages of repurposing include that approved drugs are well characterized, do not require expensive development programs needed for new drugs, and are frequently active against multiple diseases. Owing to the limited number of drugs approved to treat neglected tropical diseases (NTDs) and emerging or drug-resistant infections, healthcare practitioners use existing drugs in novel ways to treat patients with these conditions. This clinical experience, regardless of whether the outcomes are positive or negative, often is not reported or shared, and the knowledge is therefore lost. Methods: FDA and NCATS/NIH have built a pilot program called Collaborative Use Repurposing Engine (CURE) to capture and centralize the global experience of new uses of approved medical products to treat emerging threats, NTDs, and multidrug-resistant organisms. CURE includes a website (https://cure.ncats.io/ ) and a mobile app (download "PROJECT CURE" at Google Play Store). CURE provides a simple case report form for health care providers to report their experiences, and a collection of cases that have already been reported (including successful and unsuccessful treatments) which they can browse. Healthcare providers who register can also participate in a Treatment Discussion Forum, allowing for engagement with fellow clinicians. CURE could be a global network connecting major treatment centers, academics, private practitioners, government facilities, and other clinicians serving as a means of rapid communication of treatment outcomes between providers treating patients with these conditions. Results: See attached screen shots. Conclusion: Although this evidence may be insufficient to establish the safety or effectiveness of a new use for an existing product, this clinical experience may provide signals and generate hypotheses for future clinical study. It may allow for rapid identification of promising treatment approaches in urgent situations such as during outbreaks of emerging infectious threats. Disclosures: All authors: No reported disclosures.